2013
DOI: 10.1371/journal.pone.0079108
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chronic Health Conditions and Their Link with Labour Force Participation and Economic Status

Abstract: AimsTo assess the labour force participation and quantify the economic status of older Australian workers with multiple health conditions.BackgroundMany older people suffer from multiple health conditions. While multiple morbidities have been highlighted as an important research topic, there has been limited research in this area to date, particularly on the economic status of those with multiple morbidities.MethodsCross sectional analysis of Health&WealthMOD, a microsimulation model of Australians aged 45 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…For instance, a study among Australian workers with multiple health problems showed that individuals with four or more health problems were far less likely to be employed compared with those with no health condition. 11 Another study among persons with back complaints found that the co-occurrence of cardiovascular diseases resulted in a 10-fold increased risk of unemployment compared with those with back complaints alone. 12 So far, findings on the association of chronic diseases and multimorbidity with unemployment have been based mostly on self-reported health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study among Australian workers with multiple health problems showed that individuals with four or more health problems were far less likely to be employed compared with those with no health condition. 11 Another study among persons with back complaints found that the co-occurrence of cardiovascular diseases resulted in a 10-fold increased risk of unemployment compared with those with back complaints alone. 12 So far, findings on the association of chronic diseases and multimorbidity with unemployment have been based mostly on self-reported health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate analysis comparing results across the different compensation systems is not possible within the scope of this review. However, it is reasonable to infer that in cause-based systems the lack of support for those with chronic conditions, such as PMP, is a major incentive for workers to remain at work even with significant disability and pain, particularly when considering the threat of exiting the workforce on retirement wealth,9 and more so in the context of multimorbidity 8. The ratio of 4 to 10 for intervention studies from countries with cause-based systems, compared to non-cause-based or general social security systems suggests a greater incentive for interventions to be developed for workers with non-work related PMP in societies where these interventions are supported by social disability policies.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our comorbidity measure captured important dimensions of illness burden including chronicity, disability and psychiatric symptoms; counts of LLI's or specific diagnoses combinations were not captured. Since dose-response associations between the accumulation of chronic illnesses and employment exits have been observed [6,[14][15][16], a comorbidity measure which captured the number of LLI's may have identified stronger associations with specific employment exit routes. Furthermore, the measure of LLI did not exclude mental disorders, which could have led to some misclassification in the morbidity categories.…”
Section: Limitationsmentioning
confidence: 99%
“…This issue is particularly relevant among older workers since comorbidity is more prevalent in this group [11], and may increase the likelihood of employment exits due to greater disability and poorer occupational functioning [12,13]. Studies examining comorbidity as a broad construct suggest that it affects older workers' employment exits, possibly in a dose-response manner [6,8,[14][15][16][17], and additive effects of depression and heart disease on labour market participation have also been observed [18]. Yet, others have found no effect of depressive symptoms among those with chronic disease on working until retirement [4].…”
Section: Introductionmentioning
confidence: 99%